Lower incidence of inappropriate shock therapy in patients with combined cardiac resynchronisation therapy defibrillators (CRT‐D) compared with patients with non‐CRT defibrillators (ICDs). Issue 8 (22nd July 2013) - Chen, Z.; Kotecha, T.; Crichton, S.; Shetty, A.; Sohal, M.; Arujuna, A.; Kirubakaran, S.; Bostock, J.; Cooklin, M.; O'Neill, M.; Wright, M.; Gill, J. S.; et al.
Summary Introduction: A significant number of patients experience inappropriate shock therapy (IST) from implantable cardioverter‐defibrillators (ICD). An increasing number of patients with advanced heart failure receive combined ICD and cardiac resynchronisation therapy devices (CRT‐D). The incidence of IST in this group is less well described. We aimed to assess the incidence and predictors of IST in CRT‐D patients. Methods: A retrospective cohort study of prospectively collected data on patients who received an ICD and CRT‐D between October 2007 and January 2009 at our institution were studied. The primary outcome measures were the IST event rate and all‐cause mortality. Results: A total of 185 patients with ICD/CRT‐D (100/85) were included in the analysis. Eighteen patients experienced 35 episodes of IST during the follow‐up (21 ± 13 months). There was a significantly lower IST cumulative event rate in the CRT‐D vs. ICD group, 5% (CI: 1–13%) vs. 19% (95% CI: 11–30%) by 24 months, (p = 0.017). The majority of the IST was caused by atrial arrhythmias with atrial fibrillation accounting for 28 episodes of IST in nine patients. Multivariate analysis using Cox hazard model including baseline characteristics and coexisting appropriate shock therapy showed that a history of atrial fibrillation/flutter was the strongest independent predictor of IST with a hazard ratio of 3.53 (p = 0.019). Conclusion: Patients with CRT‐D had a significantly lower incidence of IST compared with patients receiving an ICD. Given that atrial arrhythmia remained the commonest trigger for IST, our finding lends support to the hypothesis that CRT may reduce atrial fibrillation burden in patients receiving CRT‐D.